PERAN DAN STRATEGI HUMAS DALAM MENINGKATKAN CITRA POSITIF TAMAN BALEKAMBANG DI MASYARAKAT KOTA SOLO - Sari, Dhika Novita (KOMUNITAS, 2014)
The Role of public relations as an agency is very crucial. It is due to the fact that if the problems appears dealing with the public so public relation has responsible to give understanding to them. Public Relation also has a very important role in conveying an understanding related to the information of the company to the public. Therefore, the role and strategy of public relations is very essential in improving the positive image of the company. This study aims to identify, to classify and to describe the role and strategy of Balekambang public relations in improving the positive image the Solo community. This study belongs to qualitative research. This research uses Kusumastuti Frida (2002 ) and Ruslan Rosad (2002 ) theories in the data analysis . The results shows that the role and strategies of public relations is success in improving the positive image of Balekambang. The role of public relations is done in Balekambang, namely (1) facilitator of communication covers receiving community complaints and facilitate communication with reporters, (2) facilitator of problems solving process by classifying the problems that not only internal but also external of Balekambang. Then, provide a solution by doing the communications between related parties, (3) communications technician in writing press releases deals with media. Meanwhile the strategies used by the Balekambang public relations are (1) holding event publications, (2) event strategy is made in order to Balekambang more widely known by the public, (3) News strategy is done by Balekambang public relation by always makes press releases about everything related to Balekambang, (4) community involvement strategy in Balekambang the public relations by holding social contact with certain communities in order to maintain a good relationship, (5) inform or image strategy ( notify the image ) the task Balekambang public relation publishes Balekambang with holding positive events, (6) lobbying and negotiation strategy, Balekambang public realation lobbies and negotiates toward the parties to conduct activities / events that can give benefit both them, and (7) social responsibility strategy, Balekambang public relation held a social event.